Spectrum of excess mortality due to carbapenem-resistant Klebsiella pneumoniae infections. (June 2016) - Hauck, C.; Cober, E.; Richter, S.S.; Perez, F.; Salata, R.A.; Kalayjian, R.C.; Watkins, R.R.; Scalera, N.M.; Doi, Y.; Kaye, K.S.; Evans, S.; Fowler, V.G.; et al.
Abstract: Patients infected or colonized with carbapenem-resistant Klebsiella pneumoniae (CRKp) are often chronically and acutely ill, which results in substantial mortality unrelated to infection. Therefore, estimating excess mortality due to CRKp infections is challenging. The Consortium on Resistance against Carbapenems in K. pneumoniae (CRACKLE) is a prospective multicenter study. Here, patients in CRACKLE were evaluated at the time of their first CRKp bloodstream infection (BSI), pneumonia or urinary tract infection (UTI). A control cohort of patients with CRKp urinary colonization without CRKp infection was constructed. Excess hospital mortality was defined as mortality in cases after subtracting mortality in controls. In addition, the adjusted hazard ratios (aHR) for time-to-hospital-mortality at 30 days associated with infection compared with colonization were calculated in Cox proportional hazard models. In the study period, 260 patients with CRKp infections were included in the BSI (90 patients), pneumonia (49 patients) and UTI (121 patients) groups, who were compared with 223 controls. All-cause hospital mortality in controls was 12%. Excess hospital mortality was 27% in both patients with BSI and those with pneumonia. Excess hospital mortality was not observed in patients with UTI. In multivariable analyses, BSI and pneumonia compared with controls were associated with aHR of 2.59 (95% CI 1.52–4.50, p <0.001) and 3.44 (95% CI 1.80–6.48, p <0.001), respectively. In conclusion, in patients with CRKp infection, pneumonia is associated with the highest excess hospital mortality. Patients with BSI have slightly lower excess hospital mortality rates, whereas excess hospital mortality was not observed in hospitalized patients with UTI.